Beyond the Borders of Femininity: St. Eugenia and St. Athanasia in Byzantine and Post-Byzantine Art - Albani, Jenny P. (Actual Problems of Theory and History of Art, 2019)
Byzantine written sources contain vitae of holy women, who disguised as monks lived for along time in monasteries or hermitages. Concealing their gender, they developed exceptional ascetic qualities surpassing their female nature. These legends, probably composed in Egypt, Syria, and Palestine, from the 5th to the 7th century, exist in Greek, Coptic, Syriac, Ethiopic, Arabic, and Latin. After the Arabs conquered these regions, Byzantine hagiography focused on other types of female saints, leaving aside holy cross-dressers.Several interpretations may be given to monastic disguises adopted by women. Virility has been associatedsince antiquity with positive qualities, while femininity with weakness and spiritual poverty. Transcending femininity was, according to Church Fathers, the only way for women to find soul salvation. On the other hand, several scholars see in the attitude of these women an attempt to imitate the superior sex and acquire equal status within the patriarchal society. The transvestite holy woman is consequently an ambiguous figure, being at the same time admired and disputed.This paper addresses issues of gender identity and iconography in Byzantine and Post-Byzantine art (6th–16th centuries), based on the figure of the transvestite female saint. Using as case studies St. Eugenia and St. Athanasia, it explores the visual language adopted by medieval artists to depict them and argues that the role of the Capital Constantinople was crucial in shaping the iconography of these holy cross-dressers. It also examines the symbolic meaning of portraits of St. Athanasia included in the otherwise conservative iconographic programmes of Byzantine and Post-Byzantine churches in Cyprus, tracing the origins of her particular popularity in the island.The image of the transvestite female saint in Byzantium challenges the accepted notions of medieval gender identity and invites us to consider an alternative version of the female persona in the Christian East. The examination of medieval depictions of St. Eugenia and St. Athanasia reveals that the iconographic rendering of these holy cross-dressers was by no means established, but rather a field of experimentation for Byzantineand Post-Byzantine painters.
Keywords: St. Eugenia; St. Athanasia; St. Andronikos; Constantinople; Cyprus; holy cross-dressers; monks